Combined adsorption - based cooling and water production - Tan, Qun Feng (2015)
Over the last few decades, researchers and scientists have been working on improvement in adsorption refrigeration technology to curb environmental problems. Funds have been allocated to school of MAE to develop an adsorption chiller by harvesting the waste heat generated by ship engines. In this project, a silica gel-water pair adsorption chiller was experimentally investigated. The experiments were first started with preliminary adsorbent bed heat transfer tests. The tests were conducted by utilising silica gel of different sizes to determine the required time for the adsorbent bed to achieve steady state in both cooling and heating processes. Next, I conducted full adsorption refrigeration cycle experiments with different particle size silica gels and different hot source temperatures while keeping the cooling water bath temperature constant. Under operating conditions of crushed silica gel adsorbent bed, 90ᵒC hot water bath temperature, 15ᵒC cooling water bath temperature, generation lift of 58.28ᵒC, 5.777×10-3 kg/s mass flow rate of water through the cooling and hot water baths, 7.669×10-3 kg/s mass flow rate of chilled water, a cooling capacity of 112.67 W, SCP of 75.11 W/kg and COP of 0.5087 can be achieved.